Análisis de potencial solar y eólico en la estación meteorológica del sector Salache. - Llumiquinga Guanoluisa, Felix Daniel (2023)
The objective of this project was to develop an analysis of the solar and wind potential in the Salache sector. This analysis was based on data collected by a weather station located in the area, addressing both weekly and monthly weather behavior. In addition, the variability in the two key seasons winter and summer is investigated: Wind speed and solar radiation emerge as crucial factors for this analysis of wind and solar potential. These data are subjected to deep scrutiny through the use of the Weibull distribution and the Normal distribution (Gaussian Bell). Utilizing computational tools like Minitab and Excel improves analysis capabilities and enables estimating the potential value that can be produced in the Salache sector. The understanding and analysis of wind speed and solar radiation, and its distribution over time, play an essential role. Therefore, this project studies the comprehensive evaluation of the energy potential of the area, supporting sustainable development and informed decision-making in the field of nonconventional renewable energy. The results obtained will provide valuable perspectives for future projects, mainly for the design and implementation of photovoltaic systems, since the wind potential does not justify its large-scale investment due to the low wind speeds that the Salache sector area presents.